The Main Character’s Struggle with External Conflict in Wonka Movie - Ni Komang Hernawati; Ni Nyoman Deni Ariyaningsih (Institut Agama Islam Negeri Palopo, 2025)
This research investigates the types of conflict the protagonist faces in the movie “Wonka.” The collected data were adopted a descriptive qualitative approach to analyze the external conflicts identified in the “Wonka” movie. Kenney’s literary theory (1966) was employed to understand the nature of the conflicts, and Thomas and Kilmann’s framework (1974) was utilized to explore the characters’ conflict resolution strategies. The results of this study indicate that the protagonist’s challenges predominantly involve external conflicts. Kenney (1966:19), in his work “How to Analyze Fiction,” defines conflict as a struggle between a principal character and another entity. External conflicts can manifest as man versus man, man versus nature, or man versus society. A total of ten instances of conflict were identified, comprising four instances of man versus man, five instances of man versus society, and one instance of man versus nature. However, this analysis will focus on three specific conflicts. Keywords: External Conflict, Main Character, Movie.